Hemodialysis-Induced Cardiac Dysfunction Is Associated with an Acute Reduction in Global and Segmental Myocardial Blood Flow - McIntyre, Christopher W. (American Society of Nephrology, 2008)
Background and objectives: Hemodialysis is associated with hemodynamic instability, acute cardiac ischemia, and the development of regional wall motion abnormalities (RWMAs). This study used serial intradialytic H(2)(15)O positron emission tomography scanning to confirm that the development of dialysis-induced RWMAs was associated with reduction in myocardial blood flow (MBF). Design, setting, participants, & measurements: Four prevalent hemodialysis patients without angiographically significant coronary artery disease had measurements of MBF during standard hemodialysis and biofeedback dialysis. All patients underwent serial measurements of MBF using positron emission tomography. Concurrent echocardiography was used to assess left ventricular function and the development of RWMAs. Hemodynamic variables were measured using continuous pulse wave analysis. Results: Mean prehemodialysis MBF was within the normal range. Global MBF was acutely reduced during hemodialysis. Segmental MBF was reduced to a significantly greater extent in areas that developed RWMAs compared with those that did not. Not all regions with reduced MBF were functionally affected, but a reduction in myocardial blood flow of >30% from baseline was significantly associated with the development of RWMAs. No significant differences in hemodynamic tolerability, RWMA development, or MBF between dialysis modalities were observed. Conclusions: Hemodialysis is associated with repetitive myocardial ischemia, which, in the absence of coronary artery disease, may be due to coronary microvascular dysfunction. Stress-induced segmental left ventricular dysfunction correlates with matched reduction in MBF. Functional poststress recovery is consistent with myocardial stunning induced by hemodialysis. This process may be important in the development of heart failure in long-term hemodialysis patients.